Em quais setores investir nos BRICs? Uma análise sob o prisma da organização industrial - Albuja, Cristian Diego (2010)
This work analyzed 2770 firms in the BRICs from 1995 until 2008 to identify the most interesting industries for investing, according to risk-return and value premises and the Industrial Organization (IO) tradition. Results support studies from Fama and French (1992), Mohanram (2005) and Goldszmidt, Brito and Vasconcelos (2007), although deviates from World Bank (2008) as to risk-return enhancing in China. Results show that the most attractive sectors for investment using the risk-return approach, filtering by value indicators, would be oil & gas in Russia and mining in Brazil, India and China, while the least interesting industries would be textile, motor vehicle parts, tools & accessories and telecommunications in Brazil.